The last utopia : human rights in history - Moyn, Samuel (Cambridge, Mass. : Belknap Press of Harvard University Press, 2010)
Human rights offer a vision of international justice that today's id ealistic millions hold dear. Yet the very concept on which the movement is based became familiar only a few decades ago when it profoundly res haped our hopes for an improved humanity. Here, historian Samuel Moyn e levates that transformation to center stage and asks what it reveals ab out the ideal's troubled present and uncertain future. It was on the ru ins of earlier political utopias, Moyn argues, that human rights achiev ed contemporary prominence. The morality of individual rights substitut ed for the soiled political dreams of revolutionary communism and natio nalism as international law became an alternative to popular struggle a nd bloody violence. But as the ideal of human rights enters into rival political agendas, it requires more vigilance and scrutiny than when it became the watchword of our hopes.--From publisher description.
Humanity before human rights -- Death from birth -- Why anticolonial ism wasn't a human rights movement -- The purity of this struggle -- In ternational law and human rights -- The burden of morality -- "Human ri ghts" in Anglo-American news -- Human rights in the 1940s -- Human righ ts between 1968-1978.
Includes bibliographical references and index.
Keywords: Human rights -- History